SISTEM PENGAMBILAN KEPUTUSAN PENENTUAN MUTASI PENDIDIK DAN TENAGA KEPENDIDIKAN MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) PADA DINAS PENDIDIKAN KOTA MALANG - Husni, Mochamad; Lestari, Elvira Verdhi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2019)
The Education Department of Malang City conduct a policy of mutation educators and educational personnel at the elementary school level by putting aside some aspects of relevance because of the shortage of employee causing conflict and various reasons candidates not doing of mutation, in addition to the a policy of mutation must continue to run the distribution of the quality of education. This study aims at the realization of a system that can help the field of Educators and Educational Personnel in Education Department of Malang City to provide solutions in the form of employee recommendations for further policy can be taken according to standard needs mutation. The decision support system method used in this research is the Weighted Product (WP) method in which each candidate of mutation will be determined based on the weight of the school data, employee data and the criteria data specified by the Education Department of Malang City, with calculations based on normalization (Wi) , multiplication until the powers of numbers to get the final rating (Vi). Data collection methods used were interviews and literature studies. The result of research of decision support system of determination of mutation of educator and educational personnel using method of Weighted Product (WP) at Malang Education Department built to give solution in the form  of recommendation of employees from each school who recommended most feasible proposed  to the a policy of mutation by the Education Department of Malang City. Keywords: Decision Support System, Employee Mutation, Education Department, Weighted Product Method, Elementary School